Adjustment of indoor temperature using internal thermal mass under different tropical weather conditions. (7th February 2020) - Wonorahardjo, Surjamanto; Sutjahja, Inge; Aisyah Damiati, Siti; Kurnia, Daniel
Abstract : According to passive design principles, room air temperature is mainly influenced by the thermal mass composition of walls and floors. This article discusses the effectiveness of thermal mass adjustment using coconut oil (co_oil) panels in a model brick house in Bandung, Indonesia. The effectiveness is determined from the improvement in air temperature profiles during the day and night under various weather conditions: clear sky, cloudy, and a combination of the two. Improvement is measured by (1) decreasing or increasing air temperature (°C h), (2) the average air temperature ( T ¯ °C), and (3) air temperature fluctuations (Δ T °C). All parameters were measured during two periods: (a) morning and afternoon and (b) 8:00 a.m. to 4:00 p.m. (working hours) and 8:00 p.m. to 6:00 a.m. (resting hours). The air temperature was measured at 30, 120, and 200 cm above floor level to determine the spatial distribution effect of thermal mass. The results that were confirmed using the simulation program Energy2D indicate that the indoor temperatures were affected by the roof insulation, envelope, and internal thermal mass (ITM). Adjustment of ITM through the addition of co_oil panels effectively improved indoor temperatures under all weather conditions, with more significant effects during clear sky weather conditions.